2018
DOI: 10.1159/000499033
|View full text |Cite
|
Sign up to set email alerts
|

Does the Beta-Lactam Matter? Nafcillin versus Cefazolin for Methicillin-Susceptible <b><i>Staphylococcus aureus</i></b> Bloodstream Infections

Abstract: Background: Antistaphylococcal penicillins have historically been regarded as the drugs of choice for methicillin-susceptible Staphylococcus aureus (MSSA) bloodstream infections (BSI). However, recent outcomes data compared to cefazolin treatment are conflicting. Objective: This study compared treatment failure and adverse effects associated with nafcillin and cefazolin for MSSA BSI. Methods: Adult inpatients with MSSA BSI between January 1, 2009 and August 31, 2015 were included in this retrospective cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The treatment of MRSA infections poses several daunting challenges. Current treatment options for MRSA infections are relatively limited and include antibiotics that are not only costly but also substantially less effective and often more toxic compared to standard antibiotic treatments for MSSA (21)(22)(23). This is in large part due to the perceived inability to use traditional ␤-lactam antibiotics for MRSA infections (2).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of MRSA infections poses several daunting challenges. Current treatment options for MRSA infections are relatively limited and include antibiotics that are not only costly but also substantially less effective and often more toxic compared to standard antibiotic treatments for MSSA (21)(22)(23). This is in large part due to the perceived inability to use traditional ␤-lactam antibiotics for MRSA infections (2).…”
Section: Discussionmentioning
confidence: 99%
“…18 Another recent retrospective study evaluating 130 patients with MSSA bacteremia at a tertiary academic medical center reported a higher incidence of nephrotoxicity with nafcillin compared with cefazolin (25% vs 2%, respectively; relative risk = 1.31), utilizing an increase in SCr ≥1.5 times or by 0.5 mg/dL from baseline levels as nephrotoxicity criteria. 19 Burrelli et al 20 reported a higher incidence of AKI with nafcillin compared with cefazolin (29.1% vs 15.4%, respectively), utilizing a definition during hospital stay with an increase in SCr ≥0.5 mg/dL or 50% increase from baseline. In contrast, Youngster et al 11 reported nafcillin AKI rates of 11.4% when used for MSSA infections in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…There remains a current debate over the most appropriate β-lactam to treat serious MSSA infections, with CFZ or OXA as the primary candidates (25, 39); most recent MSSA bacteremia studies appear to favor CFZ (16, 26, 27). Further, on balancing adverse events vs efficacy metrics, CFZ is generally regarded as a safer option, due to its decreased renal toxicity risk as compared to the antistaphylococcal penicillins (16, 27).…”
Section: Discussionmentioning
confidence: 99%